The Concept of Mediation in the Perspective of Islamic Law and Law in Indonesia - Arminsyah; Dasrianto, Vito; Mahmudi, Elva (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This research aims to explore and analyze the concept of mediation in the perspective of Islamic law and how it is applied in Indonesian legislation. The main focus is to understand the similarities and differences between the principles of mediation in Islamic law and the mediation regulations applicable in Indonesia, as well as the implications for dispute resolution. The method used in this research is a qualitative method with a descriptive-analytical approach. Data was collected through a literature study that included Islamic law literature, Indonesian legislation, and other relevant documents. The analysis was conducted by comparing the principles of mediation in Islamic law with the provisions contained in Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution and the regulations of the Supreme Court of Indonesia related to mediation. The results show that mediation in the perspective of Islamic law emphasizes the principles of justice, equality, and cooperation that are in line with sharia values. On the other hand, Indonesian legislation regulates mediation as an effective and efficient alternative to dispute resolution. Although there are some differences in the procedures and implementation, in general these two legal systems have the same goal, which is to achieve fair and peaceful dispute resolution. This research also found that the integration of the concept of mediation in Islamic law with mediation regulations in Indonesia can enrich and improve the effectiveness of dispute resolution in Indonesia.